2021
DOI: 10.1038/s41598-021-95582-7
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization and the association with hippocampal development and working memory in children with ADHD and typically-developing children

Abstract: The symptoms of hyperactivity-impulsivity and inattention displayed by children with ADHD put them at risk of experiencing peer victimization. Hippocampal maturation, may reduce a child’s vulnerability to the experience of peer victimization, as it has been associated with decreased ADHD symptomatology. Working memory is an important executive function in the formation and maintenance of social relationships, which is often impaired in ADHD. We aimed to evaluate the relationship between problem behaviours, pee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Previous studies using a variable‐centered approach showed that bullying victimization is associated with a range of emotional, behavioral, and social problems (Barker et al, 2008; Champion et al, 2003; Moore et al, 2017; Papadopoulos et al, 2021). These variations in internalizing, externalizing, and social problems associated with being a target of bullying as well as simultaneously being a target and a perpetrator might be indicative of the existence of several distinct profiles among bullied children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using a variable‐centered approach showed that bullying victimization is associated with a range of emotional, behavioral, and social problems (Barker et al, 2008; Champion et al, 2003; Moore et al, 2017; Papadopoulos et al, 2021). These variations in internalizing, externalizing, and social problems associated with being a target of bullying as well as simultaneously being a target and a perpetrator might be indicative of the existence of several distinct profiles among bullied children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that bullied children and adolescents may present mental health and social problems with varying levels of severity. Several recent studies indicate that victims of bullying can experience mild to severe hyperactivity symptoms that act as a risk factor for being bullied (Papadopoulos et al, 2021; Winters et al, 2020). Similarly, Eastman et al (2018) found that some victims of bullying show moderate depression and anxiety problems, whereas others experience severe emotional problems (Eastman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus plays a crucial role in spatial navigation and consolidation of information from short-term to long-term memory ( Bird and Burgess, 2008 ; Zhong et al, 2020 ). Studies have reported mixed findings on hippocampal morphology in ADHD patients, with some suggesting larger volumes as a compensatory reaction to impaired temporal processing ( Plessen et al, 2006 ), while others have related lower hippocampal volumes to more severe ADHD symptomatology ( Papadopoulos et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Attention deficit hyperactivity disorder (ADHD), as a common mental disorder in children, currently affects 5% of children around the world. Its symptoms are mainly inattention and hyperactivity-impulsivity [ 1 ]. Multivariate meta-regression analyses have shown that the pooled prevalence estimate of ADHD in China was 6.3% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%